Exploring Psychological Condition of Breast Cancer Survivor After Mastectomy and Chemotherapy - Yesiana Dwi Wahyu Werdani; Arief Widya Prasetya (Jurnal Kesehatan Prima, 2021)
Breast cancer becomes a frightening disease for women, it is not only physically painful but also causes psychological disorders. This study aimed to explore the psychological condition of breast cancer survivors after mastectomy and chemotherapy. This was a qualitative study with thematic analysis methods. Samples were 20 breast cancer survivors taken by purposive sampling technique based on inclusion criteria from three community health centers in Surabaya Indonesia. Ethical requirements are completed before data collection. Data collection using an in-depth interview technique and recorded by a voice recorder. Content analysis is used to process the data. This study found 2 main themes hopelessness and negative psychological well-being. On the first main theme, there was 4 sub-theme consist of worthlessness, purposeless in life, pessimistic, unhappy. While on the second main theme there were 6 sub-theme consist of worried, negative thought, irritable, negative relationship with others, denial, felt guilty. Breast cancer survivors after mastectomy and chemotherapy experience a variety of sufferings on the psychological condition and could not be able to see other good things in their life.